Comparative assessment of future solar power potential based on CMIP5 and CMIP6 multi-model ensembles - Ha, Subin; Zhou, Zixuan; Im, Eun-Soon; Lee, Young-Mi (Renewable energy, 2023)
While the popularity and feasibility of solar power have increased toward achieving a low-carbon and climate-resilient society, it is uncertain how changes in climate attributes will affect the future potential of solar power output. This study presents a comparative assessment of future changes in solar power in terms of the technology for harnessing energy from insolation (PVP vs CSP), climate projections (CMIP5 vs CMIP6), and emission scenarios. Both CMIP5 and CMIP6 multi-model projections capture the major characteristics of the global distribution seen in PVP and CSP calculated using the reanalysis data during the historical period. However, despite the general similarity to CMIP5-based results, CMIP6 models slightly outperform their CMIP5 counterparts regarding quantitative metrics and enhance the robustness of the future change signal estimated by the statistical significance and inter-model consistency. The future changes in PVP and CSP patterns are sensitive to the emission scenarios that can control the degree of warming. Under the fossil-fueled development scenarios, the greater increase in temperatures may lead to a high vulnerability of the solar power supply by reducing the output of both PVP and CSP. This study is timely and relevant to emphasizing the benefits of climate change mitigation, which can support the sustainable development of solar energy.